Institutional Capacity Building Of The Health Technology Assessment Committee Indonesian In The Implementation Of The National Health Insurance Program - Ahmad Sururi (Jurnal Manajemen Pelayanan Publik, 2023)
The institutional Indonesian Health Technology Assessment Committee or InaHTAC has not yet been fully effective and guaranteeing assessment services and recommendations for the use of health technology in the implementation of the National Health Insurance. This research aims to find out how InaHTAC institutional capacity is developed in implementing the JKN program. The theoretical framework used to analyze InaHTAC capacity building is based on the concepts of achievement of goals and institutional systems; institutional process and evaluation; productivity and sustainability. The research method applies a qualitative case study. Data collection techniques through interviews and observation. Data analysis uses systematic qualitative data analysis, namely the data classification process, categorization, and data classification process. The results and implications of the research show that developing InaHTAC's institutional capacity in implementing the JKN program needs to highlight the importance of implementing targets, quality control, and controlling costs through a strategic health casing approach. Research findings show the importance of collaborative decision-making, strengthening regulations regarding the authority of the InaHTAC institution, performance measurement, and stakeholder literacy regarding HTA through education, outreach, and continuous dissemination.